Legal grounds for exercising the right to claim compensation for damages at the expense of the state by an individual who has suffered from a criminal offence (civil law aspect) - D. V. Tymoshenko (Law and Safety)
The article identifies the legal grounds for exercising by an individual the right to claim compensation for damage caused by a criminal offence at the expense of the State (the State Budget of Ukraine), and analyses and identifies the specific features of such legal grounds. It has been noted that for compensation of damage caused to a victim as a result of a criminal offence at the expense of the State Budget of Ukraine, the mere commission of a criminal offence as the basis for civil liability is not sufficient. Therefore, additional grounds are such legal facts as failure to identify the person who committed the criminal offence or if such a person is insolvent.